Emerging concepts in heart failure treatment and management: focus on SGLT2 inhibitors in heart failure with preserved ejection fraction - Andrea Beatriz De Lorenzi; Edgardo Kaplinsky; Marx Rivera Zambrano; Laia Tomás Chaume; Joan Monell Rosas (BioExcel Publishing Ltd, 2023)
The role of sodium-glucose cotransporter 2 inhibitors (SLTG2i), developed initially as glucose-lowering agents, has represented a novelty in patients with heart failure (HF) and reduced ejection fraction (HFrEF) since dapagliflozin (DAPA-HF study) and empagliflozin (EMPERORReduced study) were able to reduce morbidity and mortality in this setting regardless of the presence or absence of diabetes. In previous large clinical trials (EMPA- REG OUTCOME study, CANVAS, DECLARE-TIMI 58), SGLT2i have been shown to attenuate HF progression expressed by reducing the risk of HF hospitalizations in patients with type 2 diabetes mellitus mostly without HF at baseline. This benefit was then corroborated with positive results in HF outcomes (cardiovascular mortality and HF hospitalizations) in patients with HF with preserved ejection fraction (HFpEF) in the EMPEROR-Preserved (empagliflozin) and DELIVER (dapagliflozin) trials. Several biological mechanisms apart from the glycosuria are attributed to these agents in this last context, including anti-inflammatory effects, reduction of fibrosis and apoptosis, improvement of myocardial metabolism, mitochondrial function optimization, and oxidative stress protection. Moreover, SGLT2i can also improve ventricular loading conditions by forcing diuresis and natriuresis, and by enhancing vascular and renal function. In addition, SGLT2i can reduce myocardial passive stiffness (diastolic function) by enforcing the phosphorylation of myofilament modulatory proteins. This article provided an overview of the main pathophysiological characteristics of HFpEF and of the diverse mechanisms of action of SGLT2i in this setting. The supporting clinical evidence of SGLT2i in HFpEF (EMPEROR-Preserved and DELIVER trials) is also reviewed. This article is part of the Emerging concepts in heart failure management and treatment Special Issue: https://www.drugsincontext.com/special_issues/emerging-concepts-in-heart-failure-management-and-treatment